MISCONCEPTION AND UNDERSTANDING OF PHOTOSYNTHETIC MATERIAL IN HIGH SCHOOLS IN PAMEKASAN REGENCY - Khairunisa Khairunisa (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
The purpose of this research is to know the misconceptions and understanding of photosynthetic material in senior high schools in Pamekasan Regency. This research uses a qualitative approach with the type of descriptive research. The selection of research subjects was carried out using a semi-structured interview technique at 5 high schools in Pamekasan Regency. Methods of collecting data by interview, observation, and documentation. Data analysis was carried out through data reduction, data display, and conclusion. The validity of the data was tested using the strangulation method. The results of the study showed that(1) SMA Nurul Hikmah achieved the highest average score of 7.8 from a score of 1-10 than other high schools, (2) three teachers and most students experienced misconceptions in the form of photosynthesis only occurs in plants that have green substances (chlorophyll) and photosynthetic materials that only depend on sunlight, (3) The understanding of teachers and students shown is a partial understanding, this means that the response given is following the specified components but is incomplete